Diuretic activity of aqueous extract and smoothie preparation of Verbesina crocata in rat (Bangladesh Journal of Pharmacology, 2018)
The aim of this study was to evaluate the diuretic activity of aqueous extract of Verbesina crocata at different doses in rat. The aqueous extract (100 and 400 mg/kg for decoction; 200 and 400 mg/kg for smoothie form), furosemide (4 mg/kg and vehicle were administered per os to rat. After 6 hours in metabolic cages, the urinary flow, glomerular ﬁltration rate and electrolyte balance (Na+ and K+) were assessed. All doses produced an increment of urinary flow and Na+/K+ excretion. Glomerular filtration rate was incremented only on smoothie form at 400 mg/kg. These findings provide a basis explaining the traditional folk medicine use of this plant as a diuretic agent.Video Clip of Methodology:Method for diuretic activity: 1 min 37 sec    Click to watch